VALUASI DENGAN METODE DIVIDEN PADA BANK PEMBANGUNAN DAERAH YANG TERCATAT DI BURSA EFEK INDONESIA - Pandu Adi Cakranegara; Kristi Indriyani (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Valuation has an important role, especially for value investors. By knowing the intrinsic value of a stock, an investor can compare it with the value formed in the market. When the intrinsic value is above the market value, the stock is undervalued and worth buying and vice versa. This study evaluates local government banks listed on the Indonesia Stock Exchange. The valuation method used is the Dividend Discount Model method. The data used is secondary data originating from financial reports and the Indonesia Stock Exchange. When the dividend discount model framework is applied, the value valuation of the bank can be obtained. The results of this study indicate that the value of Bank Jatim tends to be undervalued while Bank Jabar tends to be overvalued. It should be remembered that in conducting the assessment, there are assumptions that must be made. When this assumption is not met, the assessment results may differ.